2015
DOI: 10.1093/jxb/erv307
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution quantification of root dynamics in split-nutrient rhizoslides reveals rapid and strong proliferation of maize roots in response to local high nitrogen

Abstract: HighlightPatches rich in nitrogen are rapidly colonized by selective root growth in maize, which was quantified at high time resolution with state-of-the-art non-invasive imaging techniques in a paper-based growth system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
5
21
0
Order By: Relevance
“…the allele that increased the number of seminal roots (namely, B73) also decreased primary root size]. In line with our results, in ‘t Zandt et al (2015) observed a 2-fold increase in seminal root dry weight upon removal of primary root. The most likely explanation of these findings is the presence of a relocation mechanism for seed endosperm resources that apparently sustains root development irrespective of the genetic constraints on seminal roots.…”
Section: Discussionsupporting
confidence: 89%
“…the allele that increased the number of seminal roots (namely, B73) also decreased primary root size]. In line with our results, in ‘t Zandt et al (2015) observed a 2-fold increase in seminal root dry weight upon removal of primary root. The most likely explanation of these findings is the presence of a relocation mechanism for seed endosperm resources that apparently sustains root development irrespective of the genetic constraints on seminal roots.…”
Section: Discussionsupporting
confidence: 89%
“…However, in ‘t Zandt et al [29] found no direct dependence of the dynamic of roots exposed to differential N supply in the rhizoslides concluding that the responses on either side occurred largely independent from each other.…”
Section: Resultsmentioning
confidence: 99%
“…However, in 7- or 14-day-old rice seedling, local nitrate supply only affected elongation of LRs on primary and seminal roots, and LR number was not changed ( Wang et al , 2002 ). In 7-day-old maize seedlings, only elongation of LRs on primary roots is induced ( P. Yu et al , 2014 ), but older maize seedlings show alterations in the density and length of LRs on crown roots by local nitrate treatment ( in ‘t Zandt et al , 2015 ). Thus, the LRs of various cereal species respond differently to nitrate, implying that both species-specific and developmental stage-specific effects are involved.…”
Section: Lateral Root and Root Hair Development Response To External mentioning
confidence: 99%